Facial Palsy Induced by Covaxin in Adolescent Female - A Rare Case Report - Chaudhari, Priyanka J.; Chawda, Uditkumar Bhupeshkumar; Bhad, Bhagirath Jayantilal; Mevada, Ashvin Vasantlal; Jha, Sushilkuamar Gopikant (Current Drug Safety, 2023)
Background: The world has seen nearly 2 years of a pandemic caused by the SARS-CoV-2 virus, notoriously known as COVID-19. Several vaccines have been approved under Emergency Use Authorization (EUA) to combat the disease, one of which is Covaxin, an inactivated adjuvant SARSCoV- 2 vaccine that is generally well tolerated and has fewer side effects. However, we recently have seen a rare case of facial palsy (paralysis) following Covaxin vaccination in an adolescent girl. Case Presentation: A 16 years old adolescent girl presented with chief complaints of left side deviation of mouth with difficulty in closing right eye after 29 days of receiving the first dose of Covaxin, which was finally diagnosed as a
Keywords: adjuvant